Factors Determining Demand for Consumer Goods Among Urban Refugees - Immaculate A Niyonsaba (Uganda Christian University, 2024)
This dissertation investigates the factors determining demand for consumer goods among urban refugees.. Through a comprehensive analysis of data collected from a sample population, the study examines remittance patterns, utilization, and their impact on household well-being. The findings reveal diverse sources and frequencies of remittance inflows, with significant contributions to meeting essential expenses and supporting income-generating activities. Remittance-receiving households exhibit higher levels of income, food security, and access to education and healthcare services compared to non-recipient households. Despite challenges such as high transaction costs and limited financial literacy, remittances play a crucial role in enhancing the socio-economic resilience and long-term prospects of urban refugee households. These findings contribute to a deeper understanding of the dynamics shaping refugee livelihoods and underscore the importance of targeted interventions to optimize the impact of remittance in poverty alleviation efforts.